FACTORS AND IMPORTANCE OF FORMING PERSONAL CONSCIOUSNESS IN THE INFORMATION SOCIETY (American Journal of Pedagogical and Educational Research, 2023)
This article is devoted to the modern meanings of the formation of individual consciousness in the information society, especially representatives of the vulnerable segment of the population in the socio-psychological provision of sustainable development of society in the era of globalization: In addition, the author gives scientific interpretations by foreign and Uzbek scientists of the concept of the information society. It is concluded that in the context of the expansion of the information space, the individual not only receives free access to information, but also becomes the object of information influence. Under these conditions, the danger of alienation of the individual from society and culture increases.